Concise syntheses and some biological activities of dl‐2, 5‐di‐O‐methyl‐chiro‐inositol, dl‐1, 4‐di‐O‐methyl‐scyllo‐inositol, and dl‐1, 6‐dibromo‐1, 6‐dideoxy‐2, 5‐di‐O‐methyl‐chiro‐inositol. Issue 2 (30th September 2020) - Aksu, Kadir; Akincioglu, Hulya; Gulcin, Ilhami; Kelebekli, Latif
Abstract: The regio‐ and stereospecific synthesis of O ‐methyl‐ chiro ‐inositols and O ‐methyl‐ scyllo ‐inositol was achieved, starting from p ‐benzoquinone. After preparing dimethoxy conduritol‐B as a key compound, regiospecific bromination of the alkene moiety of dimethoxy conduritol‐B and acid‐catalyzed ring opening of dimethoxydiacetate conduritol‐B epoxide with Ac2 O afforded the desired new chiro ‐inositol derivatives and scyllo ‐inositol derivative, respectively. Spectroscopic methods were employed for the characterization of all synthesized compounds. The novel inositols (11 –17 ) had effective inhibition profiles against human carbonic anhydrase isoenzymes I and II (hCA I and II) and acetylcholinesterase (AChE). The novel inositols 11 –17 were found to be effective inhibitors against AChE, hCA I, and hCA II enzymes. K i values were calculated in the range of 87.59 ± 7.011 to 237.95 ± 17.75 μM for hCA I, 65.08 ± 12.39 to 538.98 ± 61.26 μM for hCA II, and 193.28 ± 43.13 to 765.08 ± 209.77 μM for AChE, respectively. Also, due to the inhibitory effects of the novel inositols 11 –17 against the tested enzymes, these novel inositols are potential drug candidates to treat some diseases such as glaucoma, epilepsy, leukemia, and Alzheimer's disease. Abstract : The regio‐ and stereospecific synthesis of O ‐methyl‐ chiro ‐inositols and O ‐methyl‐ scyllo ‐inositol was achieved, starting from p ‐benzoquinone. The novel inositols 11 –17 showed an effective inhibition of human carbonic anhydrase isoenzymes I and II (hCA I and II) and acetylcholinesterase (AChE), making them potential drug candidates to treat diseases such as glaucoma, epilepsy, leukemia, and Alzheimer's disease.